2012
DOI: 10.3892/etm.2012.822
|View full text |Cite
|
Sign up to set email alerts
|

Determination of oxidative stress and activities of antioxidant enzymes in guinea pigs treated with haloperidol

Abstract: Guinea pigs (Cavia porcellus) were treated with haloperidol (HP), and free radical (FR) and ferric reducing antioxidant power (FRAP) assays were used to determine oxidative stress levels. Furthermore, the superoxide dismutase (SOD), glutathione reductase (GR) and glutathione-S-transferase (GST) activity levels were detected and glucose levels and the reduced and oxidized glutathione (GSH/GSSG) ratio were measured in HP-treated and untreated guinea pigs. The present study demonstrated that the administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Antioxidant enzyme activities in plasma are commonly determined in animal experiments to examine the induction of oxidative stress by toxicants or diseases and protective effects of natural compounds of plant origin [ 65 , 66 , 67 , 68 , 69 , 70 ]. Conversely to the findings in tissues, ROT did not affect any of the enzymes assayed what could be ascribed to the low level of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzyme activities in plasma are commonly determined in animal experiments to examine the induction of oxidative stress by toxicants or diseases and protective effects of natural compounds of plant origin [ 65 , 66 , 67 , 68 , 69 , 70 ]. Conversely to the findings in tissues, ROT did not affect any of the enzymes assayed what could be ascribed to the low level of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Catalase completes the detoxification process initiated by SOD by reducing hydrogen peroxide (H 2 O 2 ) into water and molecular oxygen (Chelikani, Fita, & Loewen, 2004;Marklund, Midander, & Westman, 1984). GSTs are enzymes that catalyze the conjugation of GSH to electrophilic substrates, thus producing compounds that are generally less reactive and more soluble (Gumulec et al, 2013). The antioxidant activity of taurine was found to be associated with an improved mitochondrial function where it serves as a regulator of mitochondrial protein synthesis and enhances electron transport chain activity preventing oxidant production (Jong, Azuma, & Schaffer, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Another way through which haloperidol leads to oxidative stress phenomena is related to its ability to modulate cell metabolism; in fact, it has been shown that the treatment with this drug is also able to induce mitochondrial activity that in turn leads to an enhancement of ROS production in the whole blood of rats [ 108 ]. In an in vivo study carried out by Gumulec et al using guinea pigs ( Cavia porcellus ) treated with haloperidol, two sub-groups of animals were identified according to their responses to oxidative stress; in particular, the sub-group of animals with higher haloperidol plasma levels had increased ROS production compared with the animals with lower levels of drug in their plasma [ 109 ].…”
Section: First-generation Antipsychotics (Fgas) and Oxidative Strementioning
confidence: 99%
“…In an in vivo study carried out by Gumulec et al using guinea pigs (Cavia porcellus) treated with haloperidol, two sub-groups of animals were identified according to their responses to oxidative stress; in particular, the sub-group of animals with higher haloperidol plasma levels had increased ROS production compared with the animals with lower levels of drug in their plasma [109].…”
Section: First-generation Antipsychotics (Fgas) and Oxidative Stress: The Strange Case Of Haloperidolmentioning
confidence: 99%